Relevansi Ekoteologi dan Etika Keagamaan dalam Mendorong Agenda Pembangunan Berkelanjutan (SGDs) Menuju Indonesia Emas 2045 : Studi Kasus Peran Lembaga Pendidikan Agama dalam Pemberdayaan Ekonomi Umat dan Pelestarian Lingkungan - Achmaduddin, Adam Anhari; Yusuf Zainal Abidin; Aep Kusnawan; Muhamad Zuldin (Jurnal Ilmu Sosial dan Humaniora, 2025)
Indonesia’s sustainable development towards the Golden Indonesia 2045 Vision faces global challenges, primarily the climate crisis and digital ethical dilemmas. This research aims to analyze how Ecotheology and Religious Ethics serve as moral and practical foundations for integrating environmental issues and community welfare into the SDGs agenda (Suryadi, 2021, p. 50). The paper employs a qualitative literature review methodology using normative-theological and sociological approaches, referencing scientific literature, Kemenag policy documents, and case study reports on implementation models within religious educational institutions (Kemenag, 2023, p. 7).The findings indicate that religious educational institutions play a crucial role as dual change agents. First, through the implementation of Ecotheology (the concept of khalifah), these institutions effectively instill conservation awareness and mitigate climate risk (Lestari & Putra, 2022, p. 80). Second, by developing Value-Based Community Economy models (e.g., digital waste banks and agribusiness), they contribute to creating decent employment and value-driven economic growth (Amin, 2025, p. 50; BAZNAS, 2024, p. 15). It is concluded that the internalization of Ecotheological values is key to producing human resources with a holistic development ethic. The paper recommends stronger policy synergy (a Tripartite Model) to position religious institutions as centers for social-economic innovation focused on sustainability.